Implementation of Educational Values: Classical vs Contemporary Hadith Interpretation - Wahyu Sihab (Al-Fadlan: Journal of Islamic Education and Teaching, 2025)
Educational values in hadith have an important role in shaping the character of Muslims. However, there are differences in implementation between classical and contemporary interpretations, because classical interpretations are usually textual, while contemporary interpretations are more contextual. The purpose of the study is to analyze the comparison of the two approaches to get a relevant and comprehensive understanding, so that the educational values in the hadith can be applied effectively according to the needs of the times. The research method used is literature review by reviewing relevant journals, articles, books, and official documents. The results show that the analysis of traditional and contextual approaches in understanding the educational values of hadith shows the importance of adjusting the teachings to the context of the times. The traditional approach emphasizes the understanding of classical texts, while the contextual approach focuses on the application of values according to socio-cultural conditions. The combination of the two results in a comprehensive understanding that is relevant for creating adaptive learning methods that meet the challenges of the modern era.